The Role of Politeness Strategies in Psychotherapy Evidence from Client-Therapist Interactions (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper explores the usage of politeness strategies in psychotherapy sessions and their importance in establishing rapport and trust between therapists and clients. Based on a series of recorded and transcribed therapy sessions, this research uses qualitative analysis based on Brown and Levinson's (1978) politeness theory. It looks at how therapists negotiate face-threatening acts while maintaining empathetic and supportive interactions. It points out that the highest-ranking positive politeness strategies employed by therapists tend toward emphasis of solidarity and the establishment of a view by the client, whereas on the other hand, the most commanding negative ones involve hedging and making indirect requests for the need to not impose on a client's freedom. These may differ across therapy settings, different phases, or with respect to a client's condition. The study also showed that the linguistic choices importantly impact the development of therapeutic relationships and stressed the necessity of pragmatic competence in the clinical setting. This paper discusses implications for therapist training, the need for further research into cross-cultural differences in politeness strategies.